2018
DOI: 10.1164/rccm.201708-1580oc
|View full text |Cite
|
Sign up to set email alerts
|

Increased Extracellular Vesicles Mediate WNT5A Signaling in Idiopathic Pulmonary Fibrosis

Abstract: Increased EVs function as carriers for signaling mediators, such as WNT-5A, in IPF and thus contribute to disease pathogenesis. Characterization of EV secretion and composition may lead to novel approaches to diagnose and develop treatments for pulmonary fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
145
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(148 citation statements)
references
References 46 publications
3
145
0
Order By: Relevance
“…However, the more plausible explanation is that fibrotic EVs also carry profibrotic factors. In support of this, we recently reported that fibrotic EVs isolated from IPF lungs carried functional WNT5A (34), but additional protein cargoes likely exist that drive fibrogenesis. Perhaps, other noncoding RNAs, such as long noncoding RNAs, may be present that antagonize antifibrotic miRNAs, resulting in a profibrotic state.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, the more plausible explanation is that fibrotic EVs also carry profibrotic factors. In support of this, we recently reported that fibrotic EVs isolated from IPF lungs carried functional WNT5A (34), but additional protein cargoes likely exist that drive fibrogenesis. Perhaps, other noncoding RNAs, such as long noncoding RNAs, may be present that antagonize antifibrotic miRNAs, resulting in a profibrotic state.…”
Section: Discussionmentioning
confidence: 65%
“…EVs isolated from fibrotic lungs promote lung fibrosis. Recent studies have found that EVs carry profibrotic mediators that have fibrogenic consequences in vitro (34)(35)(36)(37). However, no studies to date to our knowledge have determined the in vivo effects of EVs in lung fibrosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular vessicles act as major channels in cell‐cell communication and PD‐L1 on EVs has been shown to mediate immune evasion and inhibit T cell functions . Moreover, recent studies have demonstrated (i) that in IPF there is an increased number of EVs which contribute to pulmonary fibrosis pathogenesis; and (ii) fibroblast‐derived EVs induce an invasive phenotype in recipient fibroblasts . Since TGFβ induced expression of the checkpoint inhibitor PD‐L1 which acted in a cell‐dependent/autocrine manner (Figures ), we investigated whether the expressed PD‐L1 was secreted into EVs; and if so, could such PD‐L1 act as a paracrine mediator of immune suppression and/or fibroblast migration.…”
Section: Resultsmentioning
confidence: 99%
“…23 The relevance of this finding has been proved in many models, such as pulmonary fibrosis or heart diseases. [24][25][26] Wnts may bind to lipoproteins that stabilize them as well. 19,27 Interestingly, macrophage-derived EVs carry Wnt proteins to ISCs in intestinal repair, 11 and we provide evidence that fibroblast-derived EVs transfer Wnt activity in the ISC niche in WT organoids as well.…”
Section: Discussionmentioning
confidence: 99%